2022
DOI: 10.1111/jonm.13891
|View full text |Cite
|
Sign up to set email alerts
|

Recycling, responsible consumption and nursing: A qualitative study of surgical nurses' recycling and medical waste management

Abstract: Aim This study was conducted to examine the opinions of nurses working in surgical wards on recycling and medical waste management. Background Surgical services and operating rooms are the most waste‐generating parts of health institutions. The primary purpose of waste management is to ensure waste minimization and increase recycling. Method In this qualitative study, in‐depth interviews were conducted with 15 nurses. The data were analysed by the content analysis method. The COREQ checklist was used in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Twelve studies aimed to investigate general knowledge, attitudes, and behaviours around sustainability in the workplace 60 , 64 , 66 72 , 75 , 77 , 78 . Eight were focused on specific areas of sustainability, either recycling or waste reduction/management or both 61 63 , 65 , 73 , 74 , 76 , 79 , and the remaining study investigated anaesthesia 80 . Most studies only reported barriers to change rather than facilitators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies aimed to investigate general knowledge, attitudes, and behaviours around sustainability in the workplace 60 , 64 , 66 72 , 75 , 77 , 78 . Eight were focused on specific areas of sustainability, either recycling or waste reduction/management or both 61 63 , 65 , 73 , 74 , 76 , 79 , and the remaining study investigated anaesthesia 80 . Most studies only reported barriers to change rather than facilitators.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent was ‘personnel shortage and workload’ (11 studies; 52%). This was often related to workload and time pressures in the operating theatre, which meant that, for example, waste was ‘thrown indiscriminately’ 76 .…”
Section: Resultsmentioning
confidence: 99%
“…For this study, a focus group and semi-structured interviews were conducted with healthcare workers within the United Kingdom during June and July 2023. These qualitative approaches were chosen as they have been found effective in determining attitudes and experiences within medical and social settings within previous studies [9][10][11][12]. The goal of the study was 'to explore barriers to correct medical waste segregation within the UK National Health Services (NHS) and investigate why medical waste is incorrectly identified as 'hazardous".…”
Section: Methodsmentioning
confidence: 99%
“…[9,10] used questionnaires and focus groups to interview nurses and found that they are aware of the need for sustainability and want to contribute but face many challenges. A key problem was the lack of clear instructions, training, and feedback [11,12] with 86% of nurses within one study expressing the need for refresher training [9]. Other studies also used questionnaires and focus groups to test the knowledge of healthcare workers and found them to have poor understanding around the correct disposal of waste [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is necessary that all personnel working in health institutions have received the necessary training in this regard. Nurses, who are in direct contact with the patient, assume primary roles in treatment and care practices, and make up the majority of health professionals working in health care centers, have important duties (Mir et al, 2013;Matos et al, 2018;Sürme and Maraş, 2022). For nurses, improper separation of medical wastes may result in infectious diseases or occupational accidents (Pandit et al, 2005).…”
Section: Introductionmentioning
confidence: 99%